Factors associated with the incidence of ARI disease in children under five - Rasi Rahagia; Glendy Ariando; Zusana A.Sasarari; Ari Setiawati; Indrawati Aris Tyarini (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Acute Respiratory Infections are a major health problem in children under five worldwide and the incidence of Acute Respiratory Infections in children under five can cause significant morbidity and mortality, especially in countries with limited health resources. This study aims to determine the relationship between smoking in the house and ventilation with the occurrence of ARI disease in children under five. The type of research used in research is this type of research analytical survey method with Cross cross-sectional approach. The analysis used in the p chi-square statistical test with a P value value of >0.05 The statistical test obtained smoking variables with a value of p = 0.010 and ventilation P = 0.000. It can be concluded that there is a relationship between the presence of family members who smoke and ventilation in the house with the incidence of ARI disease in children under five. To protect children under five from the risk of ARI caused by secondhand smoke in the home, necessary measures include stopping smoking, smoking outdoors, and ensuring good ventilation inside the home